Sinergismo e aditividade entre sistemas canabinoidérgico, opioidérgico e adrenérgico na modulação da nocicepção periférica em camundongos - Caio Fábio Baeta Lopes (2018)
Pathologic pain is a relevant clinical condition that affects 30% of individuals at least once in life. The therapeutic management of pain relies on a diverse repertoire of pharmaceuticals, but most of them are not enough effective or leads to diverse side effects, justifying the urge for new treatments. Despite the efforts to develop new pharmaceuticals, diverse approaches seek benefits on the co-administration of already existing analgesics, an attempt to maximize therapeutic effects and concurrently reduce side effects. In fact, that approach seeks benefits on pharmacological synergism, which can be defined as supra-additive effects associated to a certain biological response. The aim of this work was to evaluate, using isobolgraphic analysis, the synergistic effects of three antinociceptive substances, administered in binary doses, on the algesimetric test of paw withdrawal. The occurrence of GPCR heterodimers on lumbar DRG neurons was also evaluated. For that aim, Swiss male mice were treated with a cannabinoidergic CB1R agonist (anadimide, AEA), an opioidergic MOR agonist (DAMGO) and/or an adrenergic α2R agonist (xylazine, XYL), co-administered in the hindpaw of mice previously sensitized with prostaglandin E2 (PGE2). The nociceptive threshold was evaluated, and the results obtained were compared with the additive predicted effects. It was observed a profound pharmacological synergism for the antinociceptive effects of AEA+XYL and AEA+DAMGO, with combination indexes (IC) lower than 1. For DAMGO+XYL combination, the effects were additive (IC = 1). The experimental effects were significantly higher than those predicted based on Loewe’s additive principles, for all the effect levels tested (10, 30 and 50% MPE), considering the pairs AEA+XYL and AEA+DAMGO. For the pair DAMGO+XYL, experimental effects were significantly higher only for 10 and 30% MPE. The molecular foundation of such synergism was evaluated by investigating the expression of CB1R and MOR on primary afferent neurons of lumbar (L3-L5) DRGs. Both receptors are constitutively expressed on this neuron population. Moreover, those GPCRs are co-localized on cell cultures of those neurons, as revealed by an indirect Proximity Ligation Assay (PLA), capable of detect the assembly of protein heterocomplexes. Taken together, the results presented suggest synergistic antinociceptive effects for distinct combinations of substances, especially cannabinoidergic and opioidergic agoists, and such effect could be correlated to the occurrence of GPCR heterodimers.